SOCIAL DISTANCE BETWEEN RESIDENTS AND INTERNATIONAL TOURISTS: IMPLICATIONS FOR INTERNATIONAL BUSINESS - Xoliqberdiyeva Z.M; Summera, Khalid (University Research Base, 2025)
The main purpose of this study is determine the social distance between local people and international tourists, their behaviour to each other. This paper uses the social distance concept and employs a revised version of Bogardus’(Bogardus, E, S.(1933b). The social distance between local residents and international tourists significantly influences the dynamics of international business, especially within the tourism sector. This article examines how differences in culture, language barriers, and perceptions of economic inequality shape residents' attitudes toward tourists and their willingness to participate in tourism-related business activities. By applying sociocultural and business theories, the study reveals that a greater social distance often results in limited interaction and lower service quality, negatively affecting tourist satisfaction and overall business performance. In contrast, reducing social distance encourages positive interactions, improving tourist experiences and creating more opportunities for local businesses. The findings emphasize the importance of policies that promote cultural understanding, community engagement, and inclusive tourism to bridge these social gaps. This research provides valuable insights for policymakers, business owners, and other stakeholders aiming to enhance international tourism outcomes by fostering better resident-tourist relationships. Moreover, this study includes how to avoid resident- tourist conflicts and providing information about their better interactions and set up business together at the end of the reaserch paper.